O não-trabalho, cultura fabril e controle patronal na cidade-fábrica: cotidiano e lazer em Paulista-PE (1904-1958) - Silva Neto, Reginaldo Ferreira da (2022)
This dissertation studies the process of formation of the factory town of Paulista, from the relations between work, daily life and free time (non-work), between the years 1904 to 1958. The time frame covers the purchase of the first shares of CTP by Herman Lundgren in 1904, and extends until 1958, when the last census of the town was carried out by the IBGE and the last report of the 50s by CTP. The factory town of Paulista, in Pernambuco, for most of this period, belonged to the municipality of Olinda, as a district, and only became a municipality in 1935. During this period, the control of the manufacturing town was under the command of a Scandinavian family and heirs, the Lundgren family, shareholders in the first place, of the Paulista textile factory, and later, owners of the Paulista Textile Company. Built in 1891, the Paulista Textile Company became the main regulating and directing element in the lives of those who worked and lived there. With the Lundgren family at the head of the textile factory, the whole idea, planning and experience of a factory town would take shape and become more concrete. In addition to the economic and political meanings and the links around the spinning and weaving industry, social relationships and cultural spaces are evidenced in the constructions and daily experiences. In this way, the central theme of this dissertation is the construction of the space of the Paulista factory town, analyzing the relations between the Paulista Textile Company and its workers' villages, emphasizing the experiences of the workers/operators, their dependence on the factory, the several spaces of use in the factory town, and the relation of the factory, private life and free time of the workers/operators, as well as the attempts of control of this space and time by the company management. For such approaches, a variety of sources were used, such as periodicals, theses and dissertations, memorialist works, and documentaries. The investigation and observation of the documentation allowed us to expand a series of questions and perspectives, which are presented in this dissertation in three parts: the formation of the factory town, from the delineations made by the Paulista Textile Company, evident from the 1920s; the daily life, including the spaces of use, the spaces in dispute and the hierarchization of the spaces of uses and housing, between the 1920s and 1950s; and, finally, the non-work in its essence, that is, leisure, education, festivities and soccer, between the late 1920s to 1950s.